Предмет: Алгебра,
автор: lizanino
Помогите пожалуйста решить!)
(3а-а²)²-а²(а-2)(а+2)+2а(7+3а²)
konstantsya:
Спасибо за Лучший ответ)))
Ответы
Автор ответа:
1
(3а-а²)²-а²(а-2)(а+2)+2а(7+3а²) = 9а²-6а³+а^4-а²(а²-4)+14а+6а³ =
= 9а²-6а³+а^4-а^4+4a²+14а+6а³ = а^4-а^4-6а³+6а³+9а²+4a²+14а =
= 13a²+14a
= 9а²-6а³+а^4-а^4+4a²+14а+6а³ = а^4-а^4-6а³+6а³+9а²+4a²+14а =
= 13a²+14a
Похожие вопросы
Предмет: Русский язык,
автор: sakigrafff
Предмет: Математика,
автор: tsamarceva4
Предмет: Алгебра,
автор: aniymahsa
Предмет: Математика,
автор: шаха17
Предмет: Информатика,
автор: DilnazSu